Equipping Adult Learners with Basic Literacy Skills for Cognitive Sustainability in Lagos State, Nigeria - Blessing Anyikwa; Oyekunle Oyekunle Yinusa (Jurnal Pendidikan Nonformal, 2021)
Abstract  The non-literate adult citizens in Nigeria are often faced with the inability to apply mental intelligence in their lifestyles which is reducing their worth and relevance in the 21st century literate society. The study therefore, seeks to equip adult learners with basic literacy skills for cognitive sustainability in Lagos state, Nigeria. Four research questions were raised and answered; and four hypotheses were tested to guide the study. The study adopted descriptive survey research design. The instruments adopted for the study were Key Informant Interview (KII) and a Questionnaire. A 20-item questionnaire titled “Adult Learners’ Basic Literacy Skills Questionnaire”, (ALBLSQ) was developed by the researchers. The instrument was validated using content and face validity according to the standard approved by the National Mass Education Commission in Nigeria, and the State Agency for Mass Education in Lagos State, Nigeria (NMEC/NOGALSS). A total of one hundred and eighty (180) questionnaires were administered purposively to adult learners across the six NMEC/NOGALSS literacy centers in Lagos state, and one hundred and forty-five (145) were retrieved. The reliability of the instrument was confirmed using a test-retest procedure, which gave a correlation coefficient of 0.87. The data was presented using frequency distribution tables, percentages, and Bar Charts. The data was analyzed using Spearman Rank Order Correlation Coefficient and T-test statistical tools to test the hypotheses at 0.05 significance level. The study revealed that a significant difference exists between the performance of adult learners before intervention and the performance of adult learners after intervention of the adult basic literacy programme amongst others. The study concluded and recommended that the curriculum of the adult basic literacy should be designed to have a combination of English and mother tongue language as a medium of instruction in order to aid cognitive development among adult learners, inter alia.